Fat-Tail Distributions and Business-Cycle Models - Guido Ascari; Giorgio Fagiolo; Andrea Roventini (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
Recent empirical findings suggest that macroeconomic variables are seldom normally dis- tributed. For example, the distributions of aggregate output growth-rate time series of many OECD countries are well approximated by symmetric exponential-power (EP) den- sities, with Laplace fat tails. In this work, we assess whether Real Business Cycle (RBC) and standard medium-scale New-Keynesian (NK) models are able to replicate this sta- tistical regularity. We simulate both models drawing Gaussian- vs Laplace-distributed shocks and we explore the statistical properties of simulated time series. Our results cast doubts on whether RBC and NK models are able to provide a satisfactory representation of the transmission mechanisms linking exogenous shocks to macroeconomic dynamics.
Keywords: C1; E3; 330; Growth-Rate Distributions; Normality; Fat Tails; Time Series; Exponential- Power Distributions; Laplace Distributions; DSGE Models; RBC Models